The children's home network kinship navigator program improves family protective factors. (July 2021) - Littlewood, Kerry; Cooper, Lawrence; Yelick, Anna; Pandey, Abhishek
Highlights: This study provides evidence for a kinship navigator program using a randomized control trial. This study suggests that Kinship Navigator Programs can improve protective factors. Usual child welfare services may be less effective than kinship navigator programs in improving protective factors for kinship families. Abstract: Protective factors are an important resource for kinship families, especially when systems are often quick to assess risks. This study sought to test whether the Children's Home Network Kinship Navigator Program improved protective factors for kinship caregivers. More specifically, this study was interested in which types of CHN Kinship Navigator Program Groups improved the following protective factors: family functioning/resiliency, social emotional support, concrete support, child development and knowledge, and nurturing and attachment using the Protective Factors Survey with 1551 kinship caregivers. Results of the Repeated Measures ANOVA for each subscale showed statistically significant within and between group differences for kinship navigator program models on Family Functioning, Concrete Supports, Child Development, and Nurturing and Attachment. Conversely, usual care showed a decline in protective factors consistently across subscales. Results suggest that kinship navigator programs can improve protective factors for kinship families. Furthermore, replication of kinship navigator programs could build capacity in data collection and maintenance systems to gain a more complete picture about how systems of care impact the family.